2012
DOI: 10.14214/sf.910
|View full text |Cite
|
Sign up to set email alerts
|

Predicting moisture content in a pine logwood pile for energy purposes

Abstract: Determining the moisture content of naturally dried fuel stock without frequent measuring is a problem still unsolved. Modelling moisture content based on automatically captured meteorological data could provide a solution. An accurate model would allow the drying period and the point of chipping to be optimised. For the experimental study, a metal frame supported by load sensors and loaded with 17 tons of logwood was set up next to a meteorological station. A multiple linear regression model was used to link … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 10 publications
(20 reference statements)
1
16
0
1
Order By: Relevance
“…The ANOVA analysis showed significant differences in moisture content among the species (p < 0.0001; F = 8024.35). In fact, black locust is the specie with the lowest moisture content after harvesting, thus requiring less energy consumption or shorter natural-air drying period before combustion [32]. The differences obtained in the moisture content after harvesting between poplar and black locust were similar to that found by Manzone [33], while the value determined for willow is similar to that found by Eisenbies et al [34].…”
Section: Moisture Contentsupporting
confidence: 84%
“…The ANOVA analysis showed significant differences in moisture content among the species (p < 0.0001; F = 8024.35). In fact, black locust is the specie with the lowest moisture content after harvesting, thus requiring less energy consumption or shorter natural-air drying period before combustion [32]. The differences obtained in the moisture content after harvesting between poplar and black locust were similar to that found by Manzone [33], while the value determined for willow is similar to that found by Eisenbies et al [34].…”
Section: Moisture Contentsupporting
confidence: 84%
“…According to Hakkila (2004), moisture has a negative impact in regard to transport efficiency and its costs, heat value of fuel, combustion efficiency, combustion emissions, dry matter losses during storage as well as handling functionality especially during the frost period in winter. The methods of enhancing fuel quality have to be taken into account when defining the supply chain and storage of harvested biomass (Röser et al 2011) such as utilizing best natural drying seasons during spring and summer (Nurmi 1999, Nurmi & Hillebrand 2007, Pettersson & Nordfjell 2007, Erber et al 2012, having a drying period for loose logging residues on site (Jirjis 1995, Nurmi 1999, selecting feasible locations for roadside storage (Nurmi 1999, Nordfjell & Liss 2000, Nurmi & Hillebrand 2007, Fillback et al 2011) and for covering forest biomass piles at roadsides (Jirjis 1995, Nurmi & Hillebrand 2007, Röser et al 2011. With the use of these methods, the drying potential can be 20-30 percent points from the initial moisture content after harvesting.…”
Section: Fuel Quality Aspectsmentioning
confidence: 99%
“…If the material was stored longer, the moisture content would decrease and the transport capacity could increase. With natural drying, the moisture content can be lowered to 32% (Erber et al 2012). Nurmi and Hillebrand (2007) showed that it was possible to reduce the moisture content to 30%.…”
Section: Discussionmentioning
confidence: 99%